The reception of the New Testament in the Apostolic Fathers - Gregory, Andrew F.; Tuckett, Christopher M. (Oxford University Press, 2005)
The two-volume work The New Testament and the Apostolic Fathers offers a comparative study of two collections of early Christian texts: the New Testament; and the texts, which are conventionally referred to as the Apostolic Fathers. The first volume, The Reception of the New Testament in the Apostolic Fathers, presents a comprehensive and rigorous discussion of the extent to which the writings later included in the New Testament were known to and used by each of the Apostolic Fathers. Contemporary research on the textual traditions of both collections is used to address the questions of textua